The Beaver Indians. Anthropological papers of the AMNH - Goddard, Pliny Earle, 1869-1928. (New York : Published by order of the Trustees [of the American Museum of Natural History], 1916)
1 p. l., p.201-293. illus. Bibliography: p. 293.